A Multifunctional Skin‐Like Sensor Based on Liquid Metal Activated Gelatin Organohydrogel. Issue 30 (9th September 2022) - Xu, Shuai; Zong, Yan; Ma, Jianzhong; Liu, Leipeng
Abstract: Gelatin, as a polypeptide‐based biopolymer derived from animal resources, has a great potential to take the place of synthetic polymers for the development of next‐generation electronic skin with enhanced biocompatibility and biodegradability. However, the soft and brittle nature of polypeptide hydrogel still remains as a challenge hindering its step to achieve skin‐like properties and toward practical applications. Herein, a gelatin‐based organohydrogel using liquid metal (LM) nanodroplets as functional fillers, for the purpose of designing a multifunctional skin‐like sensor, is fabricated. The LM fillers and glycol molecules, which are introduced by solvent exchange treatment, can act as crosslinkers to establish reversible dynamic interactions with gelatin chains, thus rendering the organohydrogel with self‐healing ability and improved mechanical property very close to human skin (Young's modulus = 0.25 MPa). Being benefited from LM fillers, the developed sensor exhibits remarkable temperature sensitivity (temperature coefficient of resistance of 2.73% °C −1 ), and is capable of detecting strain changes from both subtle and large‐scale movements. The good sustainability and biocompatibility of gelatin also make the organohydrogel a green and bio‐safe sensor for wearable electronics devices. Abstract : Naturally occurring polymer from animal resource is used to develop a skin‐like sensor by using liquid metal as functional filler. The multifunctional sensor can mimic many functions of natural skin, such as sensing pressure and temperature, accurately and in real time. The as prepared sensor shows great potential as wearable electronics for motion/temperature sensing applications.